Green Synthesis Of Gold Nanoparticles As Photosensitizer For Phototherapy Breast Cancer Treatment - Al-Mafarjy, Sarah Shakir Mutar (2024)
Breast cancer is a significant cause of mortality among women, and current treatments like chemotherapy and radiotherapy can lead to severe long-term side effects. Therefore, alternative strategies are necessary. This study investigated the combined use of low-level laser therapy (LLLT) and gold nanoparticles (AuNPs) to enhance hyperthermia effects selectively in breast cancer cells. AuNPs were synthesized through a simple cost-effective method using aqueous plant extract, aiming to reduce toxicity and agglomeration issues. A novel green synthesis method utilizing Coleus scutellarioides (L.) Benth leaves was developed, and comprehensive characterization was performed. The cytotoxicity of synthesized AuNPs was evaluated using the MTT assay on human breast cancer (MDA-MB-231) and human foreskin fibroblast (Hs-27) cell lines, revealing a dose-dependent reduction in cancer cell viability within 24 hours. Subsequently, this study investigated the impact of low-level near infrared (NIR) 808 nm laser irradiation on both cell lines, with and without AuNPs. Various parameters were explored, and the presence of AuNPs significantly enhanced the effectiveness of NIR laser irradiation in inhibiting MDA-MB-231 cell growth, suggesting a promising treatment avenue. Notably, exposure of Hs-27 cells to a 300 mW laser for the double duration (10 and 15 minutes) led to less than 50% cell viability compared to the effects of other output laser powers and times used.